Asset Recovery in the German Criminal Justice System: Lights and Shadows of the New Regulation of the Confiscation of the Proceeds Of Crime - Ana E. Carrillo del Teso (Revista Brasileira de Direito Processual Penal)
In this paper, we intend to examine the highlights of the German Asset Recovery Act (Gesetz zur Reform der strafrechtlichen Vermögensabschöpfung), in force since 1st July 2017. It is a comprehensive law, with which the German legislator updated the confiscation regime in both its substantive and procedural aspects. Given the extent of this reform, we will focus on the confiscation of proceeds of crime, as it is the essence of asset recovery. Specifically, we will analyse those points of the reform emphasized by the legislator in the draft act. To this end, we will divide them between those that may seem more positive and those that are more controversial. In the first group, we will frame what refers to the position of the victims, the innovations for the decongestion of the criminal process and the regulation of the estimate of the proceeds. In the second group, we will study the new scope of the extended confiscation and the independent confiscation of assets of uncertain origin.